Role of TGFβ1 in Modulating Lipid Profile in Patients with Hashimoto’s Thyroiditis - Abed, Niran Noori; Mahdi, Prof. Dr. Elham Abed (Medical Science Journal for Advance Research, 2023)
Background:Hashimoto’s thyroiditis, an autoimmune condition primarily affecting the thyroid gland, leads to persistent inflammation and impaired thyroid function. Conversely, transforming growth factor beta-1 (TGF-β1) is a crucial protein that regulates various cellular processes, including immune responses and tissue remodeling. Present research aimed to explore the correlation between TGFβ-1 levels in Hashimoto’s Thyroiditis (HT) patients and their lipid profile levels, to achieve this. Method: A case-control study involved 90 female participants aged 20-53 years, comprising diagnosed Hashimoto’s thyroiditis patients, and an equal number of age and gender-matched healthy volunteers. The levels of TGF–β1, T3, T4, TSH, fT3, fT4, Anti TPO, Anti-TG, were investigated using the ELISA method. Moreover, the study groups’ analysis included measuring, cholesterol, TG, LDL, HDL, and vLDL using specific commercial kits. Result: The findings revealed a highly significant variation in TGFβ1 levels between the HT patients group and healthy group, highlighting the potential role of TGF-β1 in Hashimoto’s thyroiditis.emia as compared with healthy group.